Clozapine Long-Term Treatment Might Reduce Epigenetic Age Through Hypomethylation of Longevity Regulatory Pathways Genes - Pérez-Aldana, Blanca Estela; Martínez-Magaña, José Jaime; Mayén-Lobo, Yerye Gibrán; Dávila-Ortiz de Montellano, David José; Aviña-Cervantes, Carlos Luis; Ortega-Vázquez, Alberto; Genis-Mendoza, Alma Delia; Sarmiento, Emmanuel; Soto-Reyes, Ernesto; Juárez-Rojop, Isela Esther; Tovilla-Zarate, Carlos Alfonso; González-Castro, Thelma Beatriz; et al. (Frontiers in Psychiatry, 2022)
Long-term studies have shown significantly lower mortality rates in patients with continuous clozapine (CLZ) treatment than other antipsychotics. We aimed to evaluate epigenetic age and DNA methylome differences between CLZ-treated patients and those without psychopharmacological treatment. DNA methylome was analyzed using the Infinium MethylationEPIC BeadChip in 31 CLZ-treated patients with psychotic disorders and 56 psychiatric patients naive to psychopharmacological treatment. Delta age (Δage) was calculated as the difference between predicted epigenetic age and chronological age. CLZ-treated patients were stratified by sex, age, and years of treatment. Differential methylation sites between both groups were determined using linear regression models. The Δage in CLZ-treated patients was on average lower compared to drug-naive patients for the three clocks analyzed; however, after data-stratification, this difference remained only in male patients. Additional differences were observed in Hannum and Horvath clocks when comparing chronological age and years of CLZ treatment. We identified 44,716 differentially methylated sites, of which 87.7% were hypomethylated in CLZ-treated patients, and enriched in the longevity pathway genes. Moreover, by protein-protein interaction, AMPK and insulin signaling pathways were found enriched. CLZ could promote a lower Δage in individuals with long-term treatment and modify the DNA methylome of the longevity-regulating pathways genes.